Effect of short, animated storytelling, conveying the lived experiences of a mother vs a father of a trans child, on transphobia among US parents: a randomized controlled trial - Adam, Maya; Greuel, Merlin; Liu, S.; Rogge, J. R.; Martin, A.; Amsalem, D. (International journal of transgender health, 2025)
Societal transphobia fuels alarmingly high rates of suicidality among transgender and gender diverse (TGD) youth. Short, animated storytelling (SAS) videos, aimed at scaling the lived experiences of TGD youth and their families, have proven effective for reducing transphobia, while protecting the identities of the narrators. Prior research raises questions about whether gender-matching of the narrator and the viewer could impact the effectiveness of these interventions. We recruited US parents, aged 18-50, via an online academic research platform and randomized them into three groups. The two intervention arms watched an SAS video conveying the lived experiences of either a father or a mother of a transgender child. The control group read educational materials about TGD youth. We used the Transgender Stigma Scale to measure transphobia at baseline, immediately post-exposure and 30 days later. We analyzed data from 1229 participants. We found an immediate group-by-time effect (C2 = 15.6, d.f. = 2, p < 0.001) from baseline to post-intervention, in both the father’s video group (0.88 [95% CI: 0.52, 1.25]) and the mother’s video group (0.82 [95% CI: 0.51, 1.14]), when compared with the educational control group (0.004 [95% CI: −0.34, 0.35]). Although some effect remained, this was no longer significant after 30 days. We also observed a greater effect of the father’s video on transphobia reduction in male participants (0.44 [0.25] vs 1.16 [0.21]; t = 2.2, p = 0.028), while both interventions reduced transphobia in female participants. This study highlights the potential for gender-matching to enhance the effectiveness of SAS, video interventions, aimed at reducing transphobia among parents.